2004
DOI: 10.1097/01.asn.0000117287.74203.89
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation Modulates Expression and Function of Receptors and Transporters of Rat Proximal Tubules

Abstract: Abstract. Kidney transplantation often leads to disturbances of solute and volume maintenance in humans. To investigate underlying mechanisms, expression and function of renal transporters and receptors of the proximal tubule (PT) were analyzed in an acute rejection model of rat kidney transplantation. Semiquantitative RT-PCR and Western blot, histology, immunohistochemistry, and microfluorometry were performed on whole kidneys and isolated PT. With acute rejection, Na ϩ / H ϩ -exchanger type-3 (NHE-3) was mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 47 publications
5
33
0
Order By: Relevance
“…5,6 The changes in expression levels of AQP2, ENaC, and NHE3 mRNA reported in this study confirmed our previously published observations. 5,6 In this study, we have observed an increased urinary volume and Na ϩ excretion within the first 4 d after aTX and massively disturbed urinary concentrating capacity of the graft compared with sTX, indicating that this functional deterioration is solely the result of rejection. Microarray analysis showed that genes with functions related to transport were over-represented in the list of genes downregulated after aTX (Figure 2).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…5,6 The changes in expression levels of AQP2, ENaC, and NHE3 mRNA reported in this study confirmed our previously published observations. 5,6 In this study, we have observed an increased urinary volume and Na ϩ excretion within the first 4 d after aTX and massively disturbed urinary concentrating capacity of the graft compared with sTX, indicating that this functional deterioration is solely the result of rejection. Microarray analysis showed that genes with functions related to transport were over-represented in the list of genes downregulated after aTX (Figure 2).…”
Section: Discussionsupporting
confidence: 81%
“…5,6 When compared with the control group, the aTX model displayed signs of severe acute rejection characterized by massive leukocyte infiltration, as shown in Figure 1 and previously reported. 6 These changes were significantly reduced in kidneys of rats treated with CsA.…”
Section: Histologic and Functional Datamentioning
confidence: 57%
See 3 more Smart Citations